The Effects of Home-Based Exercise Training on Physical Performance, Fatigue and Quality of Life in Breast Cancer Patient Receiving Chemotherapy: A Pilot Study - Dewi, Lingga Curnia; Sukartini, Tintin; Kurniawati, Ninuk Dian; Liem, Khatijah (International Journal of Psychosocial Rehabilitation, 2020)
This study was to assess the effects of Home-Based Exercise Training (HBET) on physical performance, fatigue and quality of life on breast cancer patients receiving chemotherapy. One group pre-and post- test design. The setting of this study was in a daycare unit of Dr. Ramelan Navy Hospital Surabaya, Indonesia. 26 women with early stage of breast cancer receiving chemotherapy participated in this study. Participants completed baseline measures and waited a week after chemotherapy for exercise. Patients who were assigned to the HBET group performed 3 weeks of walking program. Test Timed Up and Go (TUG) was used to asses physical performance, while Brief Fatigue Inventory (BFI) was used to measure fatigue and The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 ( EORTC QLQ C-30) to assess the quality of life. The paired t-test showed a significant result p< 0.0001 for physical performance, fatigue and quality of life. Breast cancer patients who received HBET showed improvement in physical performance and quality of life and also reduction in fatigue. The result showed that HBET is effective in promoting and maintaining both physical performance amd quality of life, as well as reducing fatigue by increasing emotional and physical wellbeing on breast cancer patients receiving chemotherapy.